2013
DOI: 10.2134/jeq2012.0169
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Particulate Matter on California Dairy Farms

Abstract: Over the past 30 yr, individual California dairy operations have grown in size; however, little is known about the distribution and determinants of particulate matter (PM) concentrations on these dairies. Elevated exposure to PM is associated with respiratory and cardiovascular health effects, particularly in occupational settings. The purpose of this study was to quantify the concentrations of PM and all inhalable PM (0-100 µm) on California dairies. Samplers were placed at various locations (e.g., milking pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Although ruminant meat is well known for its high environmental pressures from GHGe and land use (Clark et al, 2018; Poore and Nemecek, 2018), our study has shown that actual protein intake from meat is also associated with other environmental pressures. The particulate matter (PM) production is significantly higher in the diet of people with high intake of protein from ruminant meat, with a high production of PM coming from manure (Garcia et al, 2013). It could be argued that this is not an important issue given the small percentage of particulate matter coming from agriculture compared to other sources like transport (Cambra-López et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although ruminant meat is well known for its high environmental pressures from GHGe and land use (Clark et al, 2018; Poore and Nemecek, 2018), our study has shown that actual protein intake from meat is also associated with other environmental pressures. The particulate matter (PM) production is significantly higher in the diet of people with high intake of protein from ruminant meat, with a high production of PM coming from manure (Garcia et al, 2013). It could be argued that this is not an important issue given the small percentage of particulate matter coming from agriculture compared to other sources like transport (Cambra-López et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The particulate matter (PM) production is significantly higher in the diet of people with high intake of protein from ruminant meat. This is in part ascribed to ruminant meat with a high production of PM coming from manure (Garcia et al, 2013). It could be argued that this is not an important issue given the small percentage of particulate matter coming from agriculture compared to other sources like transport (Cambra-López et al, 2010).…”
Section: Environmental Differences Between Profilesmentioning
confidence: 99%
“…However, particulate matter smaller than 2.5 μm in diameter (PM 2.5 ) is considered a health hazard to humans and animals because it can pass through the respiratory tract to the lung alveoli [1,2,3] and therefore of major interest. These fine particles can carry gases and microbes into the lung [4].…”
Section: Introductionmentioning
confidence: 99%